Does a Policy Trial Operate at the Regional Level? An Analysis of the Free Nutritional Meal Implementation Program in Malang City - Iswanto, Denny; Nashiha, Durratun; Wartana Putra, I Made Arie Widyasthana (PANGRIPTA, 2026)
This study aims to analyze the policy trial process of the Free Nutritious Meals Program (MBG) in Malang City and to evaluate its effectiveness, implementation challenges, and policy learning outcomes at the regional level. The study employs a descriptive qualitative approach using document analysis, with data collected from government regulations, official reports, scientific articles, and credible mass media sources. Data were analyzed using thematic qualitative analysis based on the policy experiment framework of Voß and Simons (2018). The findings indicate that the MBG pilot program in Malang City reflects an adaptive and evidence-based policy approach, where policies are tested on a limited scale prior to wider implementation. The program, implemented in 35 schools, demonstrates potential benefits in improving students’ nutritional intake and increasing school participation. However, several challenges persist, including delays in distribution, inconsistent nutritional quality, limited involvement of nutritionists, weak quality control, and insufficient coordination among stakeholders. Furthermore, the pilot phase serves as a policy laboratory, providing valuable insights for improving policy design, governance, and monitoring systems. This study concludes that the MBG policy trial has strategic importance in strengthening regional capacity for managing social policy innovation, although improvements in implementation and institutional coordination are required to ensure its effectiveness and sustainability.